No Relationship between the Amount of DNA Damage and the Level of hMLH1 and RASSF1A Gene Expression in Bladder Cancer Cells Treated with Cisplatin and Gemcitabine - Camargo, Elaine Aparecida de [UNESP]; Silva, Glenda Nicioli da [UNESP]; Gobette, Camila Pereira [UNESP]; Castro Marcondes, Joao Paulo de [UNESP]; Salvadori, Daisy Maria Favero [UNESP] (Asian Pacific Organization Cancer Prevention, 2013)
Tumor response to antineoplastic drugs is not always predictable. This is also true for bladder carcinoma, a highly recurrent neoplasia. Currently, the combination of cisplatin and gemcitabine is well accepted as a standard protocol for treating bladder carcinoma. However, in some cases, this treatment protocol causes harmful side effects. Therefore, we investigated the roles of the genes TP53, RASSF1A (a tumor suppressor gene) and hMLH1 (a gene involved in the mismatch repair pathway) in cell susceptibility to cisplatin/gemcitabine treatment. Two bladder transitional carcinoma cell (TCC) lines, RT4 (wild-type TP53) and 5637 (mutated TP53), were used in this study. First, we evaluated whether the genotoxic potential of cisplatin/gemcitabine was dependent on TP53 status. Then, we evaluated whether the two antineoplastic drugs modulated RASSF1A and hMLH1 expression in the two cell lines. Increased DNA damage was observed in both cell lines after treatment with cisplatin or gemcitabine and with the two drugs simultaneously, as depicted by the comet assay. A lack of RASSF1A expression and hypermethylation of its promoter were observed before and after treatment in both cell lines. On the other hand, hMLH1 downregulation, unrelated to methylation status, was observed in RT4 cells after treatment with cisplatin or with cisplatin and gemcitabine simultaneously (wild-type TP53); in 5637 cells, hMLH1 was upregulated only after treatment with gemcitabine. In conclusion, the three treatment protocols were genotoxic, independent of TP53 status. However, cisplatin was the most effective, causing the highest level of DNA damage in both wild-type and mutated TP53 cells. Gemcitabine was the least genotoxic agent in both cell lines. Furthermore, no relationship was observed between the amount of DNA damage and the level of hMLH1 and RASSF1A expression. Therefore, other alternative pathways might be involved in cisplatin and gemcitabine genotoxicity in these two bladder cancer cell lines.
Keywords: DNA damage; DNA repair; gene expression profile; genotoxicity